Development of a miniature heat exchanger for mechanically pumped loop systems for active thermal control of CubeSats - Ganzeboom, T.V.; Es, J. van; Formisani, L. (51st International Conference on Environmental Systems, 2022)
The relatively high power density of CubeSats results in large amounts of heat generated that needs to be dissipated to prevent overheating of a satellite's components. At present, passive thermal control means are used to resolve CubeSats thermal issues, however, as these satellites evolve, advanced active Thermal Control Systems (TCS) will be required. Especially the novel CubeSat propulsion systems require dedicated TCS for the propulsion unit and the corresponding electronics. A promising type of TCS for CubeSats was determined to be the Mini-Mechanically Pumped fluid Loop (Mini-MPL). One such system has been developed at the Royal Netherlands Aerospace Centre (NLR), which consists of a single phase fluid loop that is used for component cooling. One of the important components of this system is the I/F with the Payload. For this purpose a Miniature Payload Heat Exchanger (MPHX) is developed as commercially available heat exchangers are typically impractical for use in space environments. A custom design for the MPHX is presented in this paper. During the design phase, a tool which is able to evaluate the cooling performance of different MPHX models has been built. Using this tool, the three best designs in terms of cooling performance have been identified: the offset strip fin heat exchanger, and two straight channels configurations with respectively triangular and trapezoidal cross sections. The design thermal resistance of the MPHX is in the order of 0.45 K/W with a liquid pressure drop in the order of 1 mbar. The heat exchangers are produced through additive manufacturing (using the Direct Metal Laser Melting method) which allows for greater flexibility and customization of the designs. The models are tested in a pumped fluid loop at the NLR's Thermal Management Facilities to confirm the results predicted in the design phas